PENGARUH KEMAMPUAN, DISIPLIN, DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI KANTOR WILAYAH DIREKTORAT JENDERAL PERBENDAHARAAN PROVINSI SULAWESI SELATAN - Pagiu, Chrismesi (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
This study aims to identify and analyze the significant positive effect on the perfornance of work ability, a significant positive in the performance of work discipline, and a significant positive effect on the performance of work motivation employee Regional Office General of Treasury, South Sulawesi Province. The number of samples in this research are 65 respondents taken from the census techniques. The method used in this research is quantitative, with multiple linear regression approach, and t-test. Appropriate with this method, the obtained of the results that the ability is a positive and significant effect on the employee work performance of the Directorate General of Treasury, South Sulawesi Province as evidenced by the results tcount >ttable and significant <0,05, work discipline is a significant and positive effect on the employee work performance of the Directorate General of Treasury, South Sulawesi Province as evidenced by the results tcount >ttable and significant <0,05, as well as work motivation is positive and significant effect on the employee work performance of the Directorate General of Treasury, South Sulawesi Province as evidenced by the results tcount >ttable and significant <0,05. The conclusion of this study that partially of ability, discipline, and work motivation is a positive and significant impact on the employee work performance of the Directorate general of Treasury, South Sulawesi Province.